Risco regulatório no processo de gestão de riscos corporativos: um estudo no setor de energia elétrica após a implantaçao da medida provisória Nº. 579, de 11 de Setembro de 2012 - Vicente, José Antonio Caseiro (2014)
After the intervention of the federal government, with the announcement of the Provisional Act no. 579 of September 11, 2012, converted into Law no. 12.783, on January 11, 2013, there was a change in the rule for renewal of concessions to be expired between 2015 and 2017, and the perception of the increase and the importance of regulatory risk. This dissertation aimed to examine how the companies operating in the Brazilian electricity sector are addressing regulatory risk in the context of corporate governance. In order to achieve this, a qualitative research, including an initial sample of sixty-six (66) companies, was developed. Based on the highest levels of commitment to corporate governance and sustainability according to the São Paulo Stock Exchange, a careful selection was then made, resulting in nine (9) companies to develop the study. It is worth mentioning that such companies have representativeness and integrate the BOVESPA Energy Index (IEE). Primary data was obtained through interviews with eight (08) risk managers, and then compared to secondary data collected from reports released and published in the capital market, making it possible to identify and analyze how regulatory risk is being managed in the process of risk management. Once the key contribution of this dissertation was to provide a broad overview and reflection of the Brazilian reality on the evolution of form and structure that regulatory risk is managed in the corporate governance process, it is suggested that the knowledge process of risk governance be strengthened, as well as the risks be treated according to the productive segments of the Brazilian electricity sector. In conclusion, there is not a closed and definitive model; it is proposed that the risk management processes be reviewed in order to identify and quantify the acceptable levels and the vulnerability of risks when allied with strategic objectives by presenting relevant issues for future studies related to regulatory risks and the ongoing process of intelligence risk